Evaluation of the results of fixation of femoral shaft non-union with Implant failure by Sign Inter Locking Intra Medullary Nail (Journal of Dhaka National Medical College & Hospital, 2016)
This prospective study of "Evaluation of the result of fixation of femoral shaft nonunion with implant failure by SIGN interlocking intra medullarly nail" was carried out during the period of July 2007 to June 2009 at National Institute of Traumatology and Orthopedic Rehabilitation(NITOR), Dhaka, Bangladesh. Mean age of the patients was 38 years. Majority of the patients were male. Among 10 cases 8 were found injury was high energy trauma due to motor vehicle accident and there was a preponderance of fracture on the right side Removal of the previous implant, refer shinning of the fracture ends, open reduction and fixation either antegrade or retrograde SIGN interlocking intramedullary nail depend on the site of involvement The mean union time was 16 weeks. Reaming materials was used as internal bone graft and one patient developed deep infection with poor union status. Functional outcome was analyzed by Thoresen classification system. Excellent functional outcome was found in 5 (50%) cases, good in 3 (30%) cases, fair in 1 (10%) case and poor in 1 (10%) case. The final outcome satisfactory result was found in 8 (80%) cases and unsatisfactory result in 2 (20%) casesJ. Dhaka National Med. Coll. Hos. 2016; 22 (02): 28-30